Anxiety for coronavirus in adults who go to a Health Center in Los Olivos - Munguia Ramirez, Paola Adriana (2021)
Objectives: It was to determine the anxiety for coronavirus in adults who go to a Health Center in Los Olivos. Materials and methods: The methodological approach of this study was quantitative and its design was descriptive-cross-sectional. The population consisted of 150 adults. The technique used was the survey and the measurement instrument was the Coronavirus Anxiety Scale (CAS), which presents 5 statements or items, which evaluate coronavirus anxiety through symptoms. Results: Regarding the participant's age, the minimum was 30 and the maximum 59 years, the mean age being 38.63 years. Regarding anxiety, the final value without dysfunctional anxiety predominated with 94% (N = 141), followed by dysfunctional anxiety in 6% (N = 9). Regarding symptoms, in dizziness prevalence without dysfunctional anxiety with 89.3% (N = 134), in sleep disorder without dysfunctional anxiety with 81.3% (N = 122), in tonic immobility without dysfunctional anxiety with a 90.7% (N = 136), in loss of appetite without dysfunctional anxiety with 92.7% (N = 139) and in abdominal discomfort without dysfunctional anxiety with 90% (N = 135). Conclusions: Regarding anxiety due to coronavirus, it predominated without dysfunctional anxiety followed by dysfunctional anxiety. According to the symptoms, the final value without dysfunctional anxiety predominated in all of them.